Exploring generalisation processes following lexical retrieval intervention in primary progressive aphasia - Beales, A.; Cartwright, Jade; Whitworth, Anne; Panegyres, P. (Informa Healthcare, 2016)
© 2016 The Speech Pathology Association of Australia Limited Purpose: Within the current literature, positive intervention effects demonstrate the significant potential for people with Primary Progressive Aphasia (PPA) to learn/relearn words. Generalisation of intervention effects to other words and/or other contexts, however, remains unclear. Method: This multiple baseline, case-series design investigated the effects of a self-cueing lexical retrieval intervention across word classes (nouns, verbs and adjectives) on four individuals with PPA, three suggestive of the semantic variant and one of the logopenic variant. The intervention integrated semantic, phonological and orthographic levels of language production and drew on autobiographical memory. Changes in accuracy in retrieving treated and untreated items (pre-intervention, post-intervention and 4-weeks maintenance) were determined using the Cochran’s Q test, with follow-up McNemar pairwise comparisons. Result: All participants showed significant improvements in naming treated items, across all word classes. Different patterns of generalised improvement to untreated words were found for each participant. In discourse, the semantic variant participants demonstrated a significant increase in correct information units, in contrast to the participant with the logopenic variant who remained stable. Conclusion: This study provides evidence that people with PPA can show improved lexical retrieval following intervention. The findings suggest possible differences in generalisation across word classes and according to underlying deficit.